Development of Powerpoint-Based Learning Media in the Subject of Islamic Cultural History Class VII MTs Students Al-Qashash To’bia - Anggrah, Iis; Hasbi, Hasbi; Rosdiana, Rosdiana (State Islamic Institute of Palopo, 2024)
This thesis discusses the Development of Powerpoint-Based Learning Media in the Islamic Cultural History Subject Class VII MTs Al-Qashash To'bia. This research includes research development that produces powerpoint-based learning media. The results of the study show that the powerpoint-based learning media developed is considered very feasible to be used as a learning resource in the subject of Islamic cultural history. The practicality of using powerpoint-based learning media in the material of imitating commendable behavior of khulafaur rasyidin in the subject of Islamic cultural history produced an average of 86.7% who responded in the score category of 81%-100% with very practical criteria. The powerpoint-based learning media developed is considered effective in improving students' understanding of imitating the commendable behavior of khulafaur rasyidin, judging from the average preetest on the material imitating the commendable behavior of khulafaur rasyidin with a score of 57.36, a drastic increase in the learning outcome test with an average posttest score of 91.24 with a gain value 0.79.